2012
DOI: 10.1371/journal.pone.0042264
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin is Overexpressed in Lung Adenocarcinoma and Increases Cell Growth and Proliferation in Normal Lung Cells

Abstract: BackgroundGremlin, a member of the Dan family of BMP antagonists, is a glycosylated extracellular protein. Previously Gremlin has been shown to play a role in dorsal-ventral patterning, in tissue remodeling, and recently in angiogenesis. Evidence has previously been presented showing both over- and under-expression of Gremlin in different tumor tissues. Here, we sought to quantify expression of Gremlin in cancers of the lung and performed in vitro experiments to check whether Gremlin promotes cell growth and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
2
45
1
Order By: Relevance
“…Recent studies have demonstrated upregulation of GREM 1 in a variety of human cancers (12)(13)(14)(15). In the present study, GREM1 expression did not differ statistically significantly between tumor tissue and neighboring intact tissue in PRCC patients but tumor tissue showed significantly higher GREM1 expression in CRCC patients (p=0.006).…”
Section: Discussioncontrasting
confidence: 53%
“…Recent studies have demonstrated upregulation of GREM 1 in a variety of human cancers (12)(13)(14)(15). In the present study, GREM1 expression did not differ statistically significantly between tumor tissue and neighboring intact tissue in PRCC patients but tumor tissue showed significantly higher GREM1 expression in CRCC patients (p=0.006).…”
Section: Discussioncontrasting
confidence: 53%
“…These antagonists share a common cysteine knot protein motif with BMPs and inhibit the ligands by direct binding and prevention of ligand-receptor interaction (Groppe et al 2002). Antagonists include Gremlin1, Noggin, Chordin, Ventroptin, and Brorin and play protumorigenic roles in a number of different cancer types (Namkoong et al 2006;Sneddon et al 2006;Hsu et al 2008;Secondini et al 2011;Gao et al 2012;Kim et al 2012;Mulvihill et al 2012). In examining the mRNA expression of several BMP antagonists in CSC and nonstem glioma cell populations, we found robust expression of Gremlin1 in the CSCs, with comparatively modest or absent expression of other antagonists ( Fig.…”
Section: Cscs Secrete Elevated Levels Of the Bmp Antagonist Gremlin1mentioning
confidence: 99%
“…However, these findings should not be interpreted to conclude that cases of poor prognosis have a larger population of CSCs. Gremlin 1 was found to be secreted from stromal cancer-associated fibroblast (CAFs) in colon cancer and its expression was localized to invasion fronts (24)(25)(26). On the other hand, Gremlin 1 was found to be secreted by CSCs in glioblastoma and was thought to prevent CSCs from differentiating by antagonizing the effects ofBMPs (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are members of the transforming growth factor (TGF)-β superfamily and play an essential role during development and differentiation while Gremlin 1 is also related to differentiation in combination with BMPs and its dysregulation results in developmental diseases (20)(21)(22)(23). Gremlin 1 is overexpressed in various types of human cancers (24)(25)(26). Recently several studies have demonstrated that CSCs prevent the BMP differentiating effect by secreting Gremlin 1 in glioblastoma, suggesting that Gremlin 1 plays a role in maintenance of CSC properties (27,28).…”
Section: Introductionmentioning
confidence: 99%